Development and field evaluation of a competitive ELISA to detect specific antibodies against Anaplasma marginale - Bellezze, Julio; Valentini, Beatriz Susana; Bosio, Anabela; Thompson, Carolina Soledad; Primo, María Evangelina (Elsevier, 2026)
A species-specific competitive ELISA for Anaplasma marginale antibodies detection (cELISA-sAm) was developed by using both a monoclonal antibody specific to an epitope of MSP5 of A. marginale (Am6-mAb) and adding a pre-incubation phase with the truncated MSP5 of A. centrale (tMSP5c). For the determination of the cutoff value, diagnostic sensitivity (DSe) and specificity (DSp) of cELISA-sAm, 382 samples from cattle not infected with Anaplasma spp., 237 samples from cattle naturally infected with A. marginale, and 102 samples from cattle vaccinated with A. centrale were analyzed. The infection status was established using nested PCR (nPCR) or nPCR-restriction fragment length polymorphism assay (nPCR-RFLP) as reference technique. In a field evaluation, cELISA-sAm and nPCR-RFLP were used on Anaplasma spp. positive samples by double-antigen sandwich ELISA (dasELISA) from 2 herds to confirm the A. marginale infection. The cELISA-sAm optimal cutoff value was ≥ 18 %I, with a DSe of 89.9 % and a DSp of 99.0 %. In a field evaluation, concordance between cELISA-sAm and nPCR-RFLP was 93.0 % with κ = 0.81 (95 % CI = 0.56–1.00) for A. marginale-infected cattle detection. In countries in which prevention is based on vaccination with A. centrale, the replacement of current ELISAs by this cELISA-sAm would decrease the false positive results and avoid the need of species confirmation by molecular techniques when disease control programs are performed to monitor the prevalence of A. marginale.